E-Marketing and Women Consumer Decision Making Process in Kerala - S. Soniya (International Journal of Research and Analytical Reviews, 2018)
The Internet has changed the world we live in. Never before has it been so easy to access information; communicate with people all over the globe; and share articles, videos, photos, and all manner of media. The Internet has led to an increasingly connected environment, and the growth of Internet usage has resulted in the declining distribution of traditional media: television, radio, newspapers, and magazines. Marketing in this connected environment and using that connectivity to market is e-Marketing. E-Marketing embraces a wide range of strategies, but what underpins successful e-Marketing is a user-centric and cohesive approach to these strategies. While the Internet and the World Wide Web have enabled what we call new media, the theories that led to the development of the Internet have been developing since the 1950s. This paper deals with study of E-Marketing and Women Consumer Decision Making Process in Kerala